Dissection Technique for Abdominoplasty: a Comparative Study on Avulsion Technique versus Diathermocoagulation - Ana Catarina Torres Silva (2020)
Background: Many strategies have been developed to lower the high complications rate associated with a full abdominoplasty. The dissection technique may have a role to better achieve this goal. The present study compares two different dissection techniques to perform a full abdominoplasty with Scarpa fascia preservation: avulsion technique and electrodissection. Methods: A retrospective observational cohort study was performed in two different health institutions from January 2005 to January 2019. A total of 251 patients were included: 122 patients submitted to abdominoplasty using the avulsion technique (Group A) and 129 with diathermocoagulation in coagulation mode (Group B). The latter was further divided into group B1 (57 patients with device settings according to surgeon's preferences) and B2 (72 patients with a specific regulation aiming at minimal tissue damage). Several variables were analysed: population characteristics, time of hospital stay, time to drain removal, total and daily drain output, emergency department visits, readmission, reoperation, local and systemic complications. Results: There were no statistically significant differences between the general characteristics of both groups, except for previous abdominal surgery. The diathermocoagulation group had significantly lower length of hospital stay and time to drain removal. Moreover, these advantages were maximized when electrocautery was done with a specific low voltage setting as significant differences were found. The other outcomes were identical. Conclusions: Limiting the extension of electrodissection in the avulsion technique didn´t present any advantage. Using diathermocoagulation (coagulation mode) during a full abdominoplasty, especially when it's aimed at minimal tissue damage, reduces patients' time with drains.